2019
DOI: 10.1016/j.critrevonc.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Vinflunine in the treatment of relapsed metastatic urothelial cancer: A systematic review and meta-analysis of real-world series

Abstract: In addition to their contribution mentioned above, Aristotelis Bamias drafted the manuscript, Flora Zagouri performed the systematic review, and Kimon Tzannis performed the statistical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The baseline characteristics did not differ between the two cohorts, with the exception of worse prognostic parameters in the post-ICI cohort (higher incidence of bone metastases and prior pelvic irradiation). The data indicate maintained efficacy of third-line vinflunine in the era of immunotherapy, which appears to be comparable to that of reported clinical trials, if not slightly superior [ 9 , 10 ]. This is supported by the finding, that the remarkable CBR of 51.0% within the post-ICI cohort was around twofold higher compared with ICI-naïve-patients (25.0%).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The baseline characteristics did not differ between the two cohorts, with the exception of worse prognostic parameters in the post-ICI cohort (higher incidence of bone metastases and prior pelvic irradiation). The data indicate maintained efficacy of third-line vinflunine in the era of immunotherapy, which appears to be comparable to that of reported clinical trials, if not slightly superior [ 9 , 10 ]. This is supported by the finding, that the remarkable CBR of 51.0% within the post-ICI cohort was around twofold higher compared with ICI-naïve-patients (25.0%).…”
Section: Discussionsupporting
confidence: 79%
“…In this setting the vinca-alkaloid vinflunine represents a therapeutic option approved by the European Medicines Agency (EMA) in 2009 after the pivotal randomized phase III trial by Bellmunt et al showed a discrete OS advantage in the per protocol analysis compared to best supportive care [ 9 ]. However, lacking overall survival (OS) benefit in the intention to treat (ITT) analysis and a rather low response rate of 8.6% are the reasons why U.S. Food and Drug Administration (FDA) approval was not obtained [ 10 ] and vinflunine is not recommended by National Institute for Health and Clinical Excellence [ 11 ]. A real-world data analysis by Bamias et al showed superior efficacy with an overall response rate (ORR) of 18% and a tolerable safety profile of vinflunine in an unselected mUC population of 797 patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies neutropenia occurred in 9 to 17% of the cases. [26][27][28][29]33 The rate of anaemia and thrombocytopenia grade 3/4 of 7.7% and 15.4% under G/P in second line was relatively low and comparable to other retrospective studies. Likewise, the proportion of 38.5% of a neutropenia grade 3 was comparable to 30% and 32% in the analysis of Kanai and Sternberg et al 9,22,23,34…”
Section: Toxicitysupporting
confidence: 85%
“…Interestingly, NIVO1/IPI3 generated a particularly high ORR (38% per investigator), which is the highest ever reported for platinum pretreated disease in mUC. More importantly, median OS with NIVO1/IPI3 was shown to be 15.3 months, which is very promising, given that checkpoint inhibitor monotherapy in previously treated mUC has traditionally provided a median OS of 6.5 to 10.5 months (10). In spite of these very important results, several aspects of this study are worth discussing.…”
mentioning
confidence: 83%